2017
DOI: 10.15252/embj.201696179
|View full text |Cite
|
Sign up to set email alerts
|

OPA 1 deficiency promotes secretion of FGF 21 from muscle that prevents obesity and insulin resistance

Abstract: Mitochondrial dynamics is a conserved process by which mitochondria undergo repeated cycles of fusion and fission, leading to exchange of mitochondrial genetic content, ions, metabolites, and proteins. Here, we examine the role of the mitochondrial fusion protein optic atrophy 1 (OPA1) in differentiated skeletal muscle by reducing OPA1 gene expression in an inducible manner. OPA1 deficiency in young mice results in non-lethal progressive mitochondrial dysfunction and loss of muscle mass. Mutant mice are resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
254
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(265 citation statements)
references
References 62 publications
(102 reference statements)
11
254
0
Order By: Relevance
“…On one hand, FGF21 has gained attention for being a potential therapeutic protein for obesity and type 2 diabetes because it stimulates the oxidation of fatty acids, the production of ketone bodies, and inhibits lipogenesis . On the other hand, several reports indicate a pathophysiological role for FGF21: (i) it promotes bone loss and reduces bone mineral density; (ii) FGF21 is a stress‐induced myokine, which is released under conditions of starvation, ER stress, mitochondrial dysfunction, obesity, mitochondrial myopathies, and aging . We have recently shown that chronic elevation of muscle‐derived circulating FGF21 leads to systemic inflammation, precocious senescence, and premature death .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On one hand, FGF21 has gained attention for being a potential therapeutic protein for obesity and type 2 diabetes because it stimulates the oxidation of fatty acids, the production of ketone bodies, and inhibits lipogenesis . On the other hand, several reports indicate a pathophysiological role for FGF21: (i) it promotes bone loss and reduces bone mineral density; (ii) FGF21 is a stress‐induced myokine, which is released under conditions of starvation, ER stress, mitochondrial dysfunction, obesity, mitochondrial myopathies, and aging . We have recently shown that chronic elevation of muscle‐derived circulating FGF21 leads to systemic inflammation, precocious senescence, and premature death .…”
Section: Discussionmentioning
confidence: 99%
“…However, all the studies regarding FGF21 as a myokine revealed the endocrine signalling of FGF21, while the liver, WAT, BAT, and heart were shown to be both source and target of FGF21's autocrine/paracrine action . Therefore, that muscle‐derived FGF21 systemic contribution occur in stressed muscles is strongly supported . What is not clear is which is the functional role of FGF21 in the context of skeletal muscle homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the revision of this manuscript, two studies were published reporting the phenotype of muscle‐specific Opa1 depleted mice (Pereira et al , ; Tezze et al , ). In agreement with our data, they reported that ablation of Opa1 in skeletal muscle reduces muscle mass, and premature death.…”
Section: Discussionmentioning
confidence: 99%
“…Lipin1 deficiency in muscles shares similarities with other myopathies that are positive for Fgf21, an increasingly used biomarker (Khan et al, 2017;Tezze et al, 2017). Fgf21 is also induced in myopathies whose primary causes are mutations in mitochondrial DNA or in the mitochondrial fusion machinery (Khan et al, 2017;Pereira et al, 2017;Tezze et al, 2017). The Fgf21 promoter contains amino acid response elements (AARE) for the Atf4 and Atf6 transcription factors (Schaap et al, 2013).…”
Section: Discussionmentioning
confidence: 99%